Editorial - Pasierbek, Wit (Horyzonty Wychowania, 2017)
An outstanding philologist, Slavist, a historian of Polish literature and culture Aleksander Brückner, in The Etymological Dictionary of the Polish Language (1926-27) wrote that conscience means „to think this way or that”. This definition itself leads to a serious reverie, since we actually do not know what conscience is, though we have a hint – in conscience man ponders, belabours, judges.